An attempt to estimate the competency gap in the IT sector - Paweł Lula; Renata Oczkowska; Sylwia Wiśniewska; Katarzyna Wójcik (International Entrepreneurship Review, 2019)
Objective: The aim of this article is to determine whether there is a gap between the demand for competencies of graduates of the computer science major and their supply.